2019
DOI: 10.3390/su11195418
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance, Customer Satisfaction, and Profitability: A Study among Large U.S. Companies

Abstract: The academic community has been advocating for companies to focus on improving their environmental performance. While companies are increasingly taking environmental action driven mainly by top management commitment, there is interest in understanding whether by contributing to the sustainability of the natural environment companies can gain the satisfaction of their other stakeholders and in a manner that facilitates their competitiveness. With the use of partial least squares structural equation modeling amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 69 publications
2
28
1
Order By: Relevance
“…In PLS-SEM, maximizing the dependent variables’ variance explained is the main objective (Hair et al , 2012a). Thus, studies using PLS-SEM frequently do not focus on model fit but on optimizing the prediction of endogenous variables (De Mendonca and Zhou, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In PLS-SEM, maximizing the dependent variables’ variance explained is the main objective (Hair et al , 2012a). Thus, studies using PLS-SEM frequently do not focus on model fit but on optimizing the prediction of endogenous variables (De Mendonca and Zhou, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The use of outsourcing as an FM strategy in SMs is not new. Outsourcing is increasingly becoming popular among SMs (Toe, 2015;Doamekpor, 2016;Amos and Gadzekpo, 2016;De Mendonca and Zhou, 2019). This approach to FM in SMs has been associated with various advantages such as cost saving (Tayauova, 2012;Amos and Gadzekpo, 2016); stronger competitive advantage for businesses using the buildings in their core activities (Amos and Gadzekpo, 2016;Ikediashi, 2014); flexibility to change services or service providers (Amos and Gadzekpo, 2016); and the potential to increase productivity and operational efficiencies of the organisation (Amos and Gadzekpo, 2016;Cotts et al, 2010;Gilley and Rashid, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the growing concern of environmentalism, consumers are more interested in purchasing products and services that have little impact on the environment [11]. In addition, different studies have concluded that the environmental image of an organization can improve sales and competitiveness, while satisfying consumers [30,31]. Accordingly, the search for new information on various aspects of green banks has increased among consumers in the recent era, which indicates that consumers are concerned enough to monitor environmental practices of an organization [32].…”
Section: Introductionmentioning
confidence: 99%